2014
DOI: 10.1158/0008-5472.can-13-2994
|View full text |Cite|
|
Sign up to set email alerts
|

EGFR Activation and Signaling in Cancer Cells Are Enhanced by the Membrane-Bound Metalloprotease MT4-MMP

Abstract: MT4-MMP (MMP-17) is a glycosylphosphatidyl inositol-anchored matrix metalloprotease expressed on the surface of cancer cells that promotes tumor growth and metastasis. In this report, we identify MT4-MMP as an important driver of cancer cell proliferation through CDK4 activation and retinoblastoma protein inactivation. We also determine a functional link between MT4-MMP and the growth factor receptor EGFR. Mechanistic experiments revealed direct association of MT4-MMP and its positive effects on EGFR phosphory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
61
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(66 citation statements)
references
References 49 publications
3
61
0
1
Order By: Relevance
“…Previous studies have shown that MT4 promotes tumor growth and metastasis and influences cell proliferation. Pave et al [43] reported that MT4 promotes cancer cell proliferation in vivo and in vitro by promoting an outside-in signaling through the EGFR pathway. Based on this information, the differentially miRNAs evaluated in the present study may be involved in cell proliferation, differentiation, and apoptosis, as well as the growth and development of hair follicles in Hu sheep lambskin.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that MT4 promotes tumor growth and metastasis and influences cell proliferation. Pave et al [43] reported that MT4 promotes cancer cell proliferation in vivo and in vitro by promoting an outside-in signaling through the EGFR pathway. Based on this information, the differentially miRNAs evaluated in the present study may be involved in cell proliferation, differentiation, and apoptosis, as well as the growth and development of hair follicles in Hu sheep lambskin.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently identified the membrane type-4 matrix metalloproteinase (MT4-MMP or MMP17) as a new EGFR partner (Paye et al , 2014). Membrane type-4 matrix metalloproteinase belongs to the family of MT MMP that are tethered to the cell membrane through a trans-membrane domain (MT1-MMP, MT2-MMP, MT3-MMP and MT5-MMP) or a glycosylphosphatidylinositol anchor (MT4-MMP and MT6-MMP).…”
mentioning
confidence: 99%
“…Although the involvement of MMPs in cancer progression is well recognised and documented (Kessenbrock et al , 2010; Noel et al , 2012), only a few clinical and experimental studies report on MT4-MMP roles in cancer. Among the MMP family, MT4-MMP displays unique features and contributes to different steps of cancer progression through proteolytic and non-proteolytic functions (Chabottaux et al , 2006, 2009; Host et al , 2012; Paye et al , 2014). Membrane type-4 matrix metalloproteinase internalisation and recycling rely on a unique CLIC/GEEK pathway dependent on cdc-42 (Truong et al , 2016).…”
mentioning
confidence: 99%
See 2 more Smart Citations